Evaluation of acrylamide and selected parameters in some Turkish coffee brands from the Turkish market - Akgun, Banu; Arici, Muhammet (TAYLOR & FRANCIS LTD, 2019)
The purpose of this study was to measure acrylamide (AA) levels and selected parameters of different traditional Turkish coffees. AA, 5-hydroxymethylfurfural (HMF), total reducing sugar, protein, pH, moisture, dry matter (DM) as well as ash, caffeine and soluble solids content (SSC) in DM, L*, a*, b* colour parameters of coffee samples were determined and the correlation between AA level and these parameters were investigated. A total of 36 coffee samples (20 Turkish, 8 Dibek and 8 Terebinth coffee) from the Turkish market were examined. A liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was validated for the detection and quantitation of AA in coffee samples. The calibration curve was linear (R(2)0.999) over the range of 30-1000 g kg(-1). The limit of detection (LOD) and limit of quantification (LOQ) were found as 4.6 g kg(-1) and 15.5 g kg(-1), respectively. The amounts of AA in analysed coffee samples were in the range 31.1 +/- 0.6 to 323.4 +/- 5.4 mu g kg(-1). The highest mean AA levels were found in Terebinth coffees (240.3 g kg(-1)) followed by Turkish coffees (204.3 mu g kg(-1)) and then Dibek coffees (78.6 mu g kg(-1)). No tested Turkish coffee samples had an AA concentration above the indicative value (450 mu g kg(-1)) for roast coffee recommended by the European Commission (EC) in 2011. In addition, a strong positive correlation was found between HMF values and AA amounts of selected coffee types.
Keywords: Acrylamide; Turkish coffees; LC-MS; MS; HMF; caffeine; physical properties; chemical composition; COLOR CHANGES; POTATO; ANTIOXIDANT; IMPACT; ACID; Chemistry; Food Science & Technology; Toxicology